Mitigation of Water Deficit in Two Cultivars of Panicum maximum by the Application of Silicon - Rocha, Juan Ricardo [UNESP]; de Mello Prado, Renato [UNESP]; de Cassia Piccolo, Marisa (Springer Nature, 2022)
Silicon (Si) is known as an attenuator for water deficit through increasing water status. The mechanisms involved in Si to mitigate this stress may be linked to decreasing oxidative stress and increasing phenolic compounds, associated with stoichiometric homeostasis of carbon (C), nitrogen (N), and Si, although there is a lack of research especially in forage crops. This research aimed to evaluate whether the supply of Si via fertigation improves the antioxidant defense system and modifies the C/N/Si stoichiometry and the growth of two cultivars of Panicum maximum cultivated under two soil water regimes (70 and 40% water retention capacity). Two experiments were developed, and the same treatments were applied using a 2 × 2 factorial arrangement, with Si applied via fertigation (2.5 mmol L−1) to the soil, while the control (without Si) was combined with two levels of soil moisture (70 and 40% of the soil water retention capacity). The two cultivars showed high accumulation of silicon in the shoot, low C content, low C/Si and C/N ratios, and high nutritional efficiency for the use of C in both water conditions. This is related to the potential of the Si to provide the greater antioxidant defense owing to higher production of phenolic compounds and decreased electrolyte leakage index. There was an increase in relative water content, leaf water potential, total chlorophyll content, and quantum efficiency of photosystem II, as shown by greater growth and dry mass production. Si application is a promising strategy to mitigate water deficit, ensuring new physiological and nutritional homeostasis, contributing to a more sustainable agriculture by means of feeding the herds that depend on pasturelands.
Keywords: Abiotic stress; Fertirrigation; Forage; Plant nutrition; Water restriction